Contextualising ethics in the practice of translator education: the case of the indigenous value system of the Basotho - Marais, Kobus (Acta Academica: Critical views on society, culture and politics, 2012)
This article develops the suggestions made in recent publications on translation studies concerning the role of the translator as an agent. The article discusses agency as a central theme in translation, and points out that it is not a value unto itself, but that it must be conceptualised within a value system. This value system, it is contended, is inculcated during the years of study at tertiary institutions. This suggests that the value system must be incorporated into the curriculum, the choice of which is left in the hands of the lecturer. Following the lead of Tymoczko, who argued for the internationalisation of translation studies, the indigenous Basotho value system and the concept of ubuntu, with its concomitant values, are explored as values that may be of interest to translation studies. If the study of translation is to be contextualised, so does ethics in translator education. The article reconsiders the implications of critical studies for ethics, arguing that it creates an impasse for human ethical action. As a value system that nurtures society and individuality, ubuntu may be a valuable alternative.